FRI0484 Impact of psoriatic arthritis on patient-reported outcomes in 5 european union countries. (15th June 2017) - Gottlieb, AB; Gratacos, J; Dikranian, A; Fallon, L; Emir, B; Smith, T; Aikman, L; Chen, L
Abstract : Objectives: This non-interventional, cross-sectional, descriptive, exploratory analysis aimed to characterise patients (pts) with psoriatic arthritis (PsA) in the 2016 National Health and Wellness Survey (NHWS) and determine the impact of treatment, or no treatment, on pt-reported outcomes. Methods: The NHWS was a self-administered, web-based, voluntary, confidential questionnaire. Stratified randomised sampling provided a representative sample of EU adults in France, Germany, Italy, Spain and UK. Respondents completing the arthritis module and reporting PsA diagnosis were stratified by: advanced therapies (tumour necrosis factor inhibitors, interleukin antagonists, phosphodiesterase-4 inhibitors) ± other drugs; other therapies (eg conventional synthetic disease-modifying antirheumatic drugs, glucocorticoids, topical medications); or no current treatment. Short Form-36 health survey (SF-36), Work Productivity and Activity Impairment questionnaire and Patient Health Questionnaire-9 (PHQ-9) responses were summarised descriptively. Results: NHWS was completed by 80, 600 adults; 947 completed the arthritis module and self-reported PsA diagnosis. Of these, 65 (7%) reported receiving advanced therapies, 274 (29%) other therapies and 608 (64%) no current treatment. Age and gender were generally balanced between the groups (mean 51–56 years; 51–64% female). More patients on advanced therapies had a body mass index ≥30 (41%) vs other therapies (34%) and no current treatment (26%). Pts on advanced therapies reported more comorbidities (mean 2.2) vs pts on other therapies (mean 1.8) and pts with no current treatment (mean 1.7). More pts on advanced therapies were current smokers (49%) vs pts on other therapies (30%) and pts with no current treatment (32%). Prior to treatment with advanced or other therapies, 94% and 82% self-reported moderate or severe PsA, falling to 58% and 59%, respectively, after treatment, compared with 36% of pts with no current treatment. SF-36 scores and PHQ-9 scores did not widely vary across groups (Table 1 ). Regardless of treatment groups, pts reported >20% work loss, >45% overall work impairment and >45% activity impairment (Table 1 ). Conclusions: More than 60% of pts reporting PsA diagnosis reported no current treatment. Regardless of treatment group, pts reported >20% work loss and >45% work impairment. Among treated pts, >50% reported moderate or severe PsA, suggesting a need for overall better management of PsA to reduce the disease impact and improve quality of life. Our results are limited by self-reported PsA diagnosis, which may differ from physician-reported PsA diagnosis, and the survey being conducted in the EU only, which may differ from other parts of the world. Further statistical analyses are needed to determine differences between groups and correlation to other health indicators. Acknowledgements: This study was sponsored by Pfizer Inc. Editorial support was provided by A Pedder of CMC and was funded by Pfizer Inc. Disclosure of Interest: A. Gottlieb Grant/research support from: Abbott (AbbVie), Amgen, Baxalta, Celgene, Centocor (Janssen), Coronado, Dermira, Eli Lilly, Levia, Merck, Novartis, Pfizer Inc, Xenoport, Consultant for: Abbott (AbbVie), Actelion, Akros, Amgen, Astellas, Baxalta, Beiersdorf, Bristol-Myers Squibb, Canfite, Catabasis, Celgene, Centocor (Janssen), Coronado, CSL Behring Biotherapies for Life, Dermipsor, Eli Lilly, Genentech, GlaxoSmithKline, Incyte, Karyopharm, Meiji Seika Pharma, Mitsubishi Tanabe, Novo Nordisk, Novartis, Pfizer Inc, Takeda, TEVA, UCB, Vertex, Xenoport, J. Gratacos: None declared, A. Dikranian Consultant for: AbbVie, Mallinckrodt, Pfizer Inc, Speakers bureau: AbbVie, Amgen, Celgene, Mallinckrodt, Pfizer Inc, L. Fallon Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, B. Emir Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, T. Smith Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, L. Aikman Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, L. Chen Shareholder of: Pfizer Inc, Employee of: Pfizer Inc